VERBAL AND NONVERBAL ASPECTS IN REALIZING LANGUAGE POLITENESS IN THE FILM “SABTU BERSAMA BAPAK” MADE BY ADHITYA MULYA - Prima Gusti Yanti; Deasy Wahyu Hidayati; Nini Ibrahim (Bajang Institute, 2022)
This study aims to describe the verbal and nonverbal aspects of the Realization of Language Politeness in the film